The Principal's Strategy in Improving the Quality of Islamic Education - Muslim, Muslim; HS, Nasrul; Alfiah, Alfiah (Pascasarjana Universitas KH. Abdul Chalim, 2025)
The main issue addressed in this study is the low quality of Islamic education in several Integrated Islamic Elementary Schools (SDIT), particularly regarding managerial effectiveness, spiritual leadership, and innovative learning, which are not yet fully aligned with Islamic values. Based on this gap, the research aims to analyze the principal’s strategic role in enhancing the quality of Islamic education through transformational leadership and value-based management approaches. The subjects of this study include principals, teachers, and educational staff from selected SDITs in the Riau Archipelago. This research employs a qualitative descriptive method using in-depth interviews, observations, and documentation analysis. The findings reveal that principals apply collaborative strategies involving teachers and the community to strengthen the school’s religious culture, improve pedagogical competence, and nurture students’ Islamic character. The study concludes that effective leadership in Islamic education is not merely determined by administrative ability but also by spiritual exemplarity, value-oriented vision, and synergy between school management and the educational community. Therefore, the principal’s strategy plays a pivotal role in building an excellent, character-driven, and Islamic value–based school ecosystem.